1972
DOI: 10.1088/0026-1394/8/3/006
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the NSL Standard of EMF Using the AC Josephson Effect

Abstract: The techniques used for the monitoring of the NSL standard of emf using the ac Josephson effect are reported. The standard has been monitored since 29th May 1970 and the reported measurements span a period of 482 days. These measurements have predominantly used niobium point contact Josephson junctions operated at the 1 mV level.The mean of the set of standard cells comprising the NSL standard has been determined in terms of a 'Josephson frequency'. The value of this frequency a t the time of the NBS-NSL volt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Clarke [18] showed that the values obtained for 2e/h in lead, tin and indium are the same to within one part in lo*, and Parker et al [19] found this ratio to be independent of the type of Josephson junction, junction geometry, magnetic field and microwave power. Further experiments [20,21,221 with improved accuracy confirmed the general validity of (2.2) and theoretical investigations [23, 24, 251 also indicated that corrections to (2.2), if any, are extremely small.…”
Section: Josephson Voltage Standards -Historical Developmentmentioning
confidence: 71%
“…Clarke [18] showed that the values obtained for 2e/h in lead, tin and indium are the same to within one part in lo*, and Parker et al [19] found this ratio to be independent of the type of Josephson junction, junction geometry, magnetic field and microwave power. Further experiments [20,21,221 with improved accuracy confirmed the general validity of (2.2) and theoretical investigations [23, 24, 251 also indicated that corrections to (2.2), if any, are extremely small.…”
Section: Josephson Voltage Standards -Historical Developmentmentioning
confidence: 71%
“…Since the first single-point contact junctions, capable of producing 10 mV when irradiated with 100 GHz, were used as a voltage reference [5], JVSs have advanced substantially in terms of voltage output capability, mostly as a consequence of the progress of microelectronic fabrication technologies.…”
Section: Array Of Junctionsmentioning
confidence: 99%
“…The accuracy of the Josephson voltage-frequency relation Vϭn f /K J , and its independence from experimental conditions, such as bias current, temperature, and junction materials, have been subjected to many tests. 11,[14][15][16][17][18][19][20][21][22] No significant deviation from this relation has ever been found. In the most precise of these experiments, two Josephson de-vices are driven by the same frequency source, biased on the same step, and connected in series opposition across a small inductor.…”
Section: ͑1͒mentioning
confidence: 99%